2013
DOI: 10.1177/2051570714526328
|View full text |Cite
|
Sign up to set email alerts
|

From the Odyssey to the Iliad: Stratagems and practical skills in market-oriented ethnography

Abstract: The market-oriented ethnography process constitutes an interesting renewal in the study of consumer behaviour. The methodological and epistemological specificities of this process, part of Consumer Culture Theory (CCT), may compel researchers to adopt certain stratagems and ingenuity in order to access the field, carry out their fieldwork and report their findings. These tactics, which are rarely revealed yet constitute the ‘tricks’ of this method, are outlined in this article in the hope of providing pedagogi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Multiple data sources, multiple coding procedures as well as inter-coder interpretative analysis were used to reduce the risk of potential bias, particularly that of "going native" inherent to ethnographic studies (Robert-Demontrond et al, 2013), and interpretive problems.…”
Section: Data Collectionmentioning
confidence: 99%
“…Multiple data sources, multiple coding procedures as well as inter-coder interpretative analysis were used to reduce the risk of potential bias, particularly that of "going native" inherent to ethnographic studies (Robert-Demontrond et al, 2013), and interpretive problems.…”
Section: Data Collectionmentioning
confidence: 99%
“…Only an anthropological approach makes it possible to understand human realities as experienced by consumers with a view to extracting and interpreting their meanings. The second is determined by the particular nature of our field of research, which might be described as a 'minefield' (Robert-Demontrond et al, 2013). When adopting such an approach, the researcher's attitude is significant.…”
Section: Methodsmentioning
confidence: 99%
“…Béji-Bécheur et al (2011) have shown that an over-important emotional involvement in a sensitive terrain causes the data to be altered. On the other hand, Robert-Demontrond et al (2013) have demonstrated the dangers involved when the research object is evaded and the emotions are suppressed. Similarly, in the analytical framework where the effects of countertransference are seen as a major component with respect to the analysand (Heimann, 1960), the emotional impact felt during the collection of ethnographic data must be seen in a positive way, as a source of enrichment of the analyses (Devereux, [1967] 2014; Gemignani, 2011).…”
Section: Countertransference: From Psychoanalysis To Qualitative Resementioning
confidence: 99%
“…In this New perspectives, we have provided a definition of countertransference in the context of reflexivity, identified the main sources of the effects of countertransference (the context, the researcher's subjectivity and the intersubjectivity of the ethnographic encounter) and proposed practical recommendations. This tool box is proposed as a complement to the techniques and 'bricolages' which are often proper to qualitative methodologies (Denzin et al, 2006;Robert-Demontrond et al, 2013). Table 2.…”
Section: Issues Practicesmentioning
confidence: 99%
See 1 more Smart Citation